KAJIAN PENAMBAHAN TEPUNG TEMPE PADA PEMBUATAN KUE BASAH TERHADAP DAYA TERIMA KONSUMEN (Jurnal Teknologi Pangan, 2013)
The aim of this research to know influence of addition of tempeh flour in making cakes to consumer acceptance. The treatments using tempeh flour is 0% (as control),5%, 10%, 15%, 20% and 25% will be tested organoleptic test to taste, color, texture and flavor. These data will be  analized  with  Friedman  test.  The  result  of  research  showed  that  for  nagasari  and  kelepon the treatment of addition tempeh flour 10% and lumpia 25% with hedonic score for nagasari: taste  3.90  (like),  color  3.90  (like),  texture  3.95  (like),  flavor  3.90  (like);  for  to  kelepon:  taste 4,00 (like), color 3.95 (like), texture 4.00 (like), flavor 4.00 (like) and lumpia: taste 4.75 (very like), color 3.90 (like), texture 3.95 (like), flavor 3.60 (like).Keywords : tempeh flour, cakes, organoleptic test.